2022
DOI: 10.26719/emhj.22.020
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between maternal and fetal umbilical cord blood lead concentrations in Libya

Abstract: Background: People are exposed to lead from car exhaust fumes (leaded petrol), lead-based paints, plumbing systems, cigarette smoking, contaminated soil and dust, foods grown in polluted areas, and water sources. Among the vulnerable subpopulations are pregnant women, fetuses and infants. Aims: To estimate and correlate maternal and neonatal blood lead levels and compare these between neonates and their mothers in Tripoli and Ghadames. Methods: In this cross-sectional study, blood was collected from 120 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Children are particularly susceptible to neurological problems brought on by lead exposure because of their developing brain systems. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children are particularly susceptible to neurological problems brought on by lead exposure because of their developing brain systems. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Due to hormonal changes, deposits of lead that have been accumulating in the mother’s bones and teeth for years as a result of a polluted environment are released into her circulation during pregnancy. [ 6 7 ] Exposure to lead during a person’s prenatal and postnatal development can substantially disrupt their neurocognitive system, resulting in the onset of attention deficit hyperactivity disorder (ADHD). Lead is a neurotoxic metal.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence indicates an epidemic of lead poisoning in opium addicts in Iran [ 2 , 3 ]. Pregnant women, infants and children are among the groups vulnerable to lead [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show the contradiction between maternal and fetal plasma lead levels. In some studies, a positive and significant relationship has been reported between maternal and fetal lead levels [ 4 , 13 ]. However, other studies have the opposite opinion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation